Interstitial high-dose-rate brachytherapy using cobalt-60 source for cervical cancer: dosimetric and clinical outcomes from a single institute - Kumar, Mohan (J Contemp Brachytherapy, 2020)
PURPOSE: To record and report dosimetric and clinical outcomes of interstitial brachytherapy using cobalt-60 ((60)Co) source in cervical cancer. MATERIAL AND METHODS: Seventy patients who underwent external beam radiotherapy with dose of 45 Gy in 25 fractions, followed by interstitial brachytherapy (ISBT) 6.5 Gy × 4 fractions were included into this study. The ISBT applicators were inserted under combined spinal and epidural anesthesia. Computed tomography (CT) simulation was performed and axial CT images were transferred to treatment planning system. High-risk clinical target volume (CTV(HR)) and organs at risks (OARs) were contoured. Four fractions of 6.5 Gy were prescribed to CTV(HR) using inverse planning technique. Patients were followed-up for 3 years. Dosimetric parameters and clinical outcomes were recorded and compared with available literature. RESULTS: Seventy patients with FIGO stage IIB-IVA were included in the study. The median EQD(2) of 2 cm(3) of bladder, rectum, sigmoid and D(90) CTV(HR) were 70 Gy (53-75 Gy), 64 Gy (51-71 Gy), 48 Gy (44-72 Gy), and 77 Gy (70-86 Gy), and dose homogeneity index (DHI), dose non-uniformity ratio (DNR), coverage index (CI), overdose volume index (OI), and conformal index (COIN) were 0.58 (0.39-0.78), 0.42 (0.22-0.61), 0.87 (0.59-0.97), 0.19 (0.09-0.30) and 0.74 (0.52-0.85), respectively. Local control rate at 2 years was 87.14%. Eight patients had local recurrence and one patient had lung metastasis. Also, two patients with local recurrence had recto-vaginal fistula. Two patients had grade 2 proctitis (2.8%) and one patient developed grade 3 proctitis (1.4%). There was no grade 2 or higher bladder toxicity. CONCLUSIONS: The dosimetric parameters, local control and toxicities of high-dose-rate interstitial brachytherapy in cervical cancer patients treated by (60)Co radioactive source are similar, compared to available literature using iridium-192 ((192)Ir) source.